Effective human resource management strategy for hospital nursing organizations - Ayana Matsumoto (Management Science Letters, 2019)
Human resource management (HRM) was first developed as a corporate business strategy that aimed to retain employees in the workplace and to develop personnel who generated results and whose capabilities could be effectively utilized. In recent years, human resource perspectives have been emphasized in personnel management by hospital nursing organizations. This study examined effective HRM strategies for creating an attractive nursing practice environment from the perspec-tive of “magnetism.” A questionnaire (“32 Items Regarding Effective Human Resource Management Policies”) was developed. The Practice Environment Scale of the Nursing Work Index was employed to assess the type of environment in which nurses wished to continue working, and factors contributing to a desirable nursing practice environment were defined as “magnetic.” Analysis of data obtained from nursing managers (n=305) yielded five factors that were effective HRM policies for hospital nursing organizations. It was also shown that the nursing practice environment was made more attractive by incorporating more of these policy elements. The following six strategies were identified: (1) enhancement of personal career development and organizational develop-ment; (2) goal management and personnel evaluations to assure the quality of patient care and pro-mote team collaboration; (3) flexible hiring and transfer policies based on business execution; (4) promoting outside interactions to make the organization an open system; (5) ensuring support for career development; and (6) supporting a safe and healthy nursing practice environment by enhancement of manpower.